Engaging the history of religions - from an Islamic studies perspective - Olsson, Susanne (Temenos, 2015)
The future and relevance of the history of religions discipline in the Swedish context has been discussed lately. This article is a response to this debate from an Islamic studies perspective. The authors argue that the history of religions discipline may become more relevant if a more self-critical approach is adopted, an interdisciplinary attitude upheld, and if there is an openness to learn from other disciplines studying religion such as Islamic studies. Moreover, a reflection on ‘history’ in the history of religions is necessary if elitism and a too narrow definition of the discipline are to be avoided. Furthermore, the article addresses the question as to whether or not scholarly engagement in disseminating findings in public should be an intellectual and moral requirement.